Pengembangan Aplikasi Monitoring Program Kerja berbasis Mobile menggunakan Framework Flutter (Studi Kasus: Departemen Sistem Informasi FILKOM UB) - Muhibbuddin Al Haqqi; Issa Arwani; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The number of work programs in the Department of Information Systems (DSI) Faculty of Computer Science, Universitas Brawijaya is currently not in line with the support of an easy work program monitoring platform. Currently, the monitoring process is carried out using Google Sheets and Microsoft Excel which have several weaknesses including data that is not yet fully integrated, an unattractive appearance and difficulty in customizing the platform. Departing from these problems, this research developed a mobile-based monitoring application for departmental work programs. In this study prototyping was used as a development method, this method is very suitable because it prioritizes user needs for the application being developed. The stages of the prototyping method include initial requirements, design, prototyping, customer evaluation, review and update, development, testing and maintenance. From the results of the implementation, testing was carried out using the black box method for all functional requirements of the application, the results of which have gone well according to the desired input and output. While on the user acceptance test questionnaire, the application that has been developed has a user acceptance rate of 93,5% which is entered in very good criteria.